Effectiveness of Using Animation Videos in Science Learning in Elementary Schools: A Systematic Literature Reviews - Putri, Siti Anisa; Rohmani; Apriza, Berta; Elizar (Universitas Pendidikan Ganesha, 2024)
Science learning in elementary schools plays a crucial role in fostering students' curiosity and interest in science, developing critical and logical thinking skills, and equipping students with scientific knowledge and practical skills applicable in daily life. This study aims to analyze the effectiveness of animated videos in enhancing science learning in elementary schools through a systematic literature review. Employing the Systematic Literature Review (SLR) method, data were sourced from Google Scholar, focusing on articles published between 2019 and 2023. The review was conducted in five stages. In the initial search using the keyword